Master’s degrees at Spanish public universities: An explanatory efficiency model - Urionabarrenetxea, Sara; San-Jose, Leire; García-Merino, Jose Domingo (Journal of Management and Business Education, 2025)
Competition between universities is increasing and master's degrees are in the spotlight. The efficiency of such degrees undoubtedly affects the success of a university, so it has important implications for their prestige and the rest of university’s´ actions and strategies. This paper aims to identify which variables (both managerial and contextual) serve to improve the efficiency of a university's Master's degree offer. To that end, we use a three-step research method: first, we apply a Delphi process to identify the inputs-outputs for determining efficiency. Based on the proposals made by experts, we have developed an specific indicator called Student oriented Economic Transient Efficiency adjusted for Quality (SETEQ), which includes quality as an output. Second, a Data Envelopment Analysis (DEA) is carried out as a tool to establish an efficiency ranking of universities in regard to their master´s degrees. Third, we propose a moderation model that allows us to relate the efficiency of Master's degrees with the different strategies followed by the universities (direct management factors) in order to find out which strategies are more effective. This model includes moderating effects (contextual factors) that condition the effectiveness of these strategies Our findings show that master´s degrees are more efficient when the quality assurance system is flexible and regional authorities are proactive in education.